## Elementary Technical Mathematics

Published by Brooks Cole

# Chapter 6 - Section 6.3 - Equations with Parentheses - Exercises - Page 242: 39

x=-2

#### Work Step by Step

Simplifying 5 + 3(x + 7) = 26 + -6(5x + 11) Reorder the terms: 5 + 3(7 + x) = 26 + -6(5x + 11) 5 + (7 * 3 + x * 3) = 26 + -6(5x + 11) 5 + (21 + 3x) = 26 + -6(5x + 11) Combine like terms: 5 + 21 = 26 26 + 3x = 26 + -6(5x + 11) Reorder the terms: 26 + 3x = 26 + -6(11 + 5x) 26 + 3x = 26 + (11 * -6 + 5x * -6) 26 + 3x = 26 + (-66 + -30x) Combine like terms: 26 + -66 = -40 26 + 3x = -40 + -30x Solving 26 + 3x = -40 + -30x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '30x' to each side of the equation. 26 + 3x + 30x = -40 + -30x + 30x Combine like terms: 3x + 30x = 33x 26 + 33x = -40 + -30x + 30x Combine like terms: -30x + 30x = 0 26 + 33x = -40 + 0 26 + 33x = -40 Add '-26' to each side of the equation. 26 + -26 + 33x = -40 + -26 Combine like terms: 26 + -26 = 0 0 + 33x = -40 + -26 33x = -40 + -26 Combine like terms: -40 + -26 = -66 33x = -66 Divide each side by '33'. x = -2 Simplifying x = -2

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.